2020
DOI: 10.1016/j.isci.2020.101537
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and UV- Catalyzed Oxidation Results in Trapped Amyloid-β Intermediates Revealing that Self-Assembly Is Required for Aβ-Induced Cytotoxicity

Abstract: Dityrosine (DiY), via the cross-linking of tyrosine residues, is a marker of protein oxidation, which increases with aging. Amyloid-b (Ab) forms DiY in vitro and DiYcross-linked Ab is found in the brains of patients with Alzheimer disease. Metal-or UV-catalyzed oxidation of Ab42 results in an increase in DiY cross-links. Using DiY as a marker of oxidation, we compare the self-assembly propensity and DiY crosslink formation for a non-assembly competent variant of Ab42 (vAb) with wildtype Ab42. Oxidation results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
(122 reference statements)
0
27
0
Order By: Relevance
“…After 24 h, we observed that the DiY signal intensity reaches a plateau after about 4h incubation in both the [1-10/Cu 2+ ] and [1-10/Cu 2+ H 2 0 2 ] samples ( Figure 1 D). Together, these data reveal that tau, similar to Aβ [ 22 , 41 ] and α-synuclein [ 23 ], rapidly forms DiY in an MCO environment and that this depends on Cu 2+ concentration. Even in the absence of H 2 O 2 , supra-equimolar level Cu 2+ was able to efficiently induce DiY in dGAE.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…After 24 h, we observed that the DiY signal intensity reaches a plateau after about 4h incubation in both the [1-10/Cu 2+ ] and [1-10/Cu 2+ H 2 0 2 ] samples ( Figure 1 D). Together, these data reveal that tau, similar to Aβ [ 22 , 41 ] and α-synuclein [ 23 ], rapidly forms DiY in an MCO environment and that this depends on Cu 2+ concentration. Even in the absence of H 2 O 2 , supra-equimolar level Cu 2+ was able to efficiently induce DiY in dGAE.…”
Section: Resultsmentioning
confidence: 90%
“…In these proteins, DiY cross-links can contribute to increased mechanical strength and protein insolubility [ 54 ]. DiY cross-linking has been shown to form and influence the aggregation of both Aβ and α-synuclein in vitro under oxidative environments [ 20 , 21 , 22 , 41 ]. We have previously demonstrated that DiY cross-linking stabilises Aβ and α-synuclein fibrils in vitro and revealed the presence of DiY-cross-linked Aβ fibrils in Aβ plaques and DiY cross-linked α-synuclein in Lewy bodies [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cells were imaged at 37 °C and 5% CO 2 on Operetta CLS high-content imaging system (PerkinElmer) by using DAPI, FITC and TRITC filters. To ensure the reproducibility of the findings, three independent experiments each containing a minimum of 5000 cells were analysed using Harmony software automated analysis algorithm provided within the system [56].…”
Section: Cytotoxicity and Cell Viability Assaysmentioning
confidence: 99%
“…The cells were imaged using Operetta CLS highcontent imaging system (PerkinElmer) using DAPI, FITC and TRITC filters at 37 °C and 5% CO2. A minimum of three independent experiments each containing at least 5000 cells were analysed using the Harmony software automated analysis algorithm within the system to ensure the reproducibility of the findings [39].…”
Section: Cytotoxicity and Cell Viability Assaysmentioning
confidence: 99%